Dietary cardiovascular risk factors and serum cholesterol in an Old Order Mennonite community. - Glick, M (1998)
OBJECTIVES: Dietary and coronary heart disease risk factors in Old Order Mennonite men and women were examined. METHODS: A food frequency questionnaire was mailed to 250 Mennonites who had participated in a previous study of coronary heart disease risk factors. RESULTS: Mennonites consumed a diet high in total fat, saturated fats, and cholesterol. Men had lower average serum cholesterol levels (174 mg/dL) than women (191 mg/dL). CONCLUSIONS: The Mennonites' diet was similar to that of the overall US population in saturated fat percentage and higher in cholesterol. Serum cholesterol levels, adiposity, and blood pressure were lower than expected among Mennonite men, perhaps because of their higher levels of physical activity.